DEVELOPMENT OF ZAKAT, INFAQ, AND SHODAQOH APPLICATION SYSTEMS IN MOSQUES IN THE COMMUNITY - Hani Fitria Rahmani; Febri Dolis Herdiani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Continuing the previous research with the title